Effect of Foliar Application of Urea on Growth and Yield of Radish (Raphanus sativus L.) under Field Conditions in Parwan, Afghanistan - Abdul Jabar Charkhi; Agha Mohammad Mohammadi (Penerbit Hellow Pustaka, 2025)
This study investigated the effect of foliar application of urea on the growth and yield of radish (Raphanus sativus L.) under field conditions in Parwan province, Afghanistan. A randomized complete block design (RCBD) with five treatments (0 g/L, 1 g/L, 2 g/L, 3 g/L, and 4 g/L urea) and three replications was used. Results indicated that foliar application of urea significantly improved plant growth and yield parameters. The highest values for plant height, leaf number, root length, root diameter, and root fresh weight were recorded at 3 g/L and 4 g/L urea concentrations, with 4 g/L producing the maximum. These findings suggest that foliar urea application enhances nitrogen use efficiency, increases radish productivity, and offers a sustainable approach to vegetable production in Afghanistan.